FRI0393 BASELINE CHARACTERISTICS OF THE STUDY POPULATION IN ROCCELLA, A PHASE 2 CLINICAL TRIAL EVALUATING THE EFFICACY AND THE SAFETY OF S201086/GLPG1972 IN PATIENTS WITH KNEE OSTEOARTHRITIS. (2nd June 2020) - Bernard, K.; Grankov, S.; Van der Stoep, M.; Lalande, A.; Imbert, O.; Phung, D.; Chimits, D.; Muller, K.; Van der Aar, E.; Deckx, H.; Pueyo, M.; Eckstein, F.
Abstract : Background: Osteoarthritis (OA) is a degenerative joint disease involving structural pathology of all joint tissues, and most commonly affecting the knee, hip and hand. Degradation of the cartilage extracellular matrix represents a central feature of OA and is widely thought to be mediated by proteinases that degrade primarily aggrecan and collagen. ADAMTS-5, a Disintegrin And Metalloproteinase with ThromboSpondin-motif-5, is a key aggrecan-cleaving enzyme involved in cartilage degradation. S201086/GLPG1972, a potent and highly selective inhibitor of ADAMTS-5, is an oral Disease-Modifying OsteoArthritis Drug (DMOAD) candidate. Objectives: The primary objective of the ROCCELLA phase 2 clinical trial (NCT03595618 ) is to evaluate the effect of S201086/GLPG1972 over 52 weeks of treatment (3 dose groups compared to placebo) in reducing cartilage loss. Cartilage thickness of the knee is being measured quantitatively by Magnetic Resonance Imaging. Here, we describe the baseline characteristics of patients included in the ROCCELLA clinical trial. Methods: The main inclusion criteria were: male or female, aged 40 to 75, with a diagnosis of knee OA according to the clinical and radiological criteria of the American College of Rheumatology. The target knee had to meet a pain score between 40 and 90 mm on a 100 mm Visual Analog Scale (VAS), and the following radiographic feature upon central radiographic readings: Kellgren/Lawrence (KL) 2 or 3 and OARSI medial joint space narrowing (JSN) 1 or 2 (for more details see Deckx et al . OARSI 2020). The rationale for these specific radiographic inclusion criteria was to ensure sufficient cartilage loss over 12 months to assess the efficacy of S201086/GLPG1972. Results: Across 12 countries, 3319 patients were screened and 932 were finally included in the study. The screen failure of 72% is mainly due to the radiological criteria. The age of the patients was 62.9 ± 7.3 years (mean ± SD) with a majority of women (69.3%). The BMI was 30.5 ± 4.7 kg/m 2 . The duration of knee OA was 7.2 ± 6.9 years. Five hundred and one (53.8%) patients reported a medical history of musculoskeletal and connective tissue disorders, mainly osteoarthritis in other sites (20.2%), back pain (13.6%), and arthralgia (9.8%). At inclusion, 97.2% of the patients were taking different types of drug treatments, mainly anti-inflammatory and anti-rheumatic products (69.4%) and analgesics (42%). At baseline, 11% of the target knees were KL2 and 89% were KL3; 32% were OARSI medial JSN grade 1 and 68% grade 2. Target knees at inclusion had a pain score on the VAS of 63.5 ± 11.4 mm (range 0-100, with 0 for no and 100 for extreme pain) and a total WOMAC (Likert 3.1) score of 48.0 ± 15.0 (range 0-96). The WOMAC subscores for pain, stiffness and physical function were 10.0 ± 3.2 (range 0-20), 4.2 ± 1.6 (range 0-8) and 33.8 ± 11.2 (range 0-68, indicating functional limitation), respectively. Conclusion: For this clinical trial, patients were selected to present radiological criteria ( i.e. OARSI JSN 1 and 2) to ensure sufficient structural progression (cartilage loss) over 12 months, as well as clinical symptoms. These stringent selection criteria were the main cause for the high screen failure rate. These baseline characteristics should warrant the ability to evaluate the efficacy of S201086/GLPG1972 as a DMOAD candidate. The search for an effective pharmacological treatment that can prevent or cure OA remains a major challenge and unmet medical need. Disclosure of Interests: Katy Bernard Employee of: Institut de Recherches Internationales Servier, Sergey GRANKOV Employee of: Institut de Recherches Internationales Servier, Marjolijne van der Stoep Employee of: Galapagos, Agnès Lalande Employee of: Institut de Recherches Internationales Servier, Olivier Imbert Employee of: Institut de Recherches Internationales Servier, De Phung Employee of: Galapagos, Damien Chimits Employee of: Institut de Recherches Internationales Servier, Karine Muller Employee of: Galapagos, Ellen van der Aar Employee of: Galapagos, Henri Deckx Employee of: Galapagos, Maria Pueyo Employee of: Institut de Recherches Internationales Servier, Felix Eckstein Grant/research support from: Merck, Orthotrphix, Servier, Galapagos, Kolon Tissuegene, Samumed, Novartis, Consultant of: Merck, Bioclinica, Servier, Samumed, Roche, Kolon Tissuegene, Galapagos and Novartis, Employee of: co-owner and employment with Chondrometrics